Adaptive performance of Indonesian Marine Corps Middle-Ranked Officers: The mediating role of job crafting on job demands and job resources - Dwi Warih Untari; Fendy Suhariadi; Andreas Budihardjo (UIN Raden Mas Said Surakarta, 2021)
Adaptive performance of Marine Corps’ Middle-Ranked Officers (Perwira Menengah Marinir) is an important indicator of the success of the Indonesian Marine Corps’s mission. High job demands and job resources indicate that the Marine Corps is a challenging organization. This study aims to provide a broader perspective on contextual antecedents of Marine Corps organization with job crafting as a mediator of job demands and job resources on the adaptive performance of Marine Corps’ Middle- Ranked Officers. This study used a quantitative approach with a questionnaire survey towards 230 Indonesian Marine Corps’ Middle-Ranked Officers. Data analysis were done using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with SPSS 22 and AMOS 5.0. Results shown that the hypothesis developed on this research study got significant support. Job demands had positive effects on adaptive performance (β = .16; p< .001); job demands had negative effects on job crafting (β = −.13, p< .01). In return, job resources had positive effects on adaptive performance (β = .59; p< .001) and job resources had positive effects on job crafting (β = .77, p< .001); job crafting had positive effects on adaptive performance (β = .39, p< .001). Effects mediated by job crafting showed a good fit, variance of the adaptive performance 80.9% and variance of job crafting 65.3%. In this case, job demands have a positive effect on the performance of Marine Corps’ Middle-Ranked Officers. Further details are explained and discussed.